A dual‐band branch line coupler based on Pi‐shaped coupled lines. Issue 2 (February 2015) - Katakam, Sri; Ren, Han; Shao, Jin; Zhou, Mi; Arigong, Bayaner; Ding, Jun; Zhang, Hualiang
ABSTRACT This article presents a coupler using Pi‐shaped coupled lines for dual‐band operations. In this design, two open circuited stubs are tapped at both ends of a coupled line structure to realize the 90° phase changes at two frequencies. The designed structure is used in place of a conventional quarter wavelength transmission line for dual‐band application. For verification, a 3‐dB branch line coupler with operating frequencies of 0.95 and 1.52 GHz is designed. The simulated and measured results are in good agreement with each other. © 2015 Wiley Periodicals, Inc. Microwave Opt Technol Lett 57:501–504, 2015